Serial evaluation of the SOFA score is reliable for predicting mortality in acute severe pancreatitis. Issue 7 (February 2018) - Tee, Yu-San; Fang, Hsin-Yueh; Kuo, I.-Ming; Lin, Yann-Sheng; Huang, Song-Fong; Yu, Ming-Chin
Abstract : Abstract: Acute severe pancreatitis caused high mortality, and several scoring systems for predicting mortality are available. We evaluated the effectiveness of serial measurement of several scoring systems in patients with acute severe pancreatitis. We retrospectively obtained serial measurements of Ranson, Acute Physiology and Chronic Health Assessment (APACHE) II, and Sequential Organ Failure Assessment (SOFA) scores of 159 patients with acute severe pancreatitis. The overall mortality rate was 20%, and early mortality (in the first 2 weeks) occurred in 10 (7.4%) patients, while late mortality occurred in 17 (12.6%). All scoring systems were reliable for predicting overall and intensive care unit mortality, while the SOFA score on day 7 presented the largest area under the receiver operator characteristic (ROC) curve (0.858, SE 0.055). Changes in scores over time were evaluated for predicting the progression of organ failure, and the change in SOFA score on hospital day 7 or no interval change in SOFA score was associated with higher mortality rates. APACHE II and SOFA scores are both sensitive for predicting mortality in acute pancreatitis. The serial SOFA scores showed reliable for predicting mortality. Hospital day 7 is a reasonable time for SOFA score reassessment to predict late mortality in acute severe pancreatitis.